Investigation of modal damping ratios for stay cables based on stochastic subspace identification with ambient vibration measurements. Issue 16 (December 2019) - Chen, Chien-Chou; Wu, Wen-Hwa; Yu, Szu-Ting; Lai, Gwolong
The stability assessment of stay cables based on the damping ratios of lower cable modes has attracted a large amount of research efforts. An accurate determination of those modal damping ratios is consequently required for the analysis or health monitoring of cable-stayed bridges. The aim of this study was to explore the challenge in accurately identifying the modal damping ratios of stay cable. The ambient vibration measurements collected from the stay cables of four cable-stayed bridges are investigated to cover different characteristics. A recently developed methodology based on stochastic subspace identification is adopted to determine the modal damping ratios of the cable. With the identified modal damping ratios for the stay cables of four bridges, comparison is made to examine the range of cable damping in different cable-stayed bridges and discuss the effects of several influence factors. It is found that the modal damping ratios for the stay cables of investigated bridges typically fall between 0% and 0.7%, close to the range from 0.05% to 0.5% reported by Post-Tensioning Institute. Moreover, it is also discovered that the modal damping ratio of the cable would decrease with increasing cable length if the energy dissipation mechanism of the cable principally comes from the anchorage device. In the cases where the middle free length section of the cable is filled with effective grouting materials, the modal damping ratio of the cable is not necessarily correlated with the cable length. Finally, the obtained results also indicate that the grouting material filled in the middle free length section of the cable defines the primary contribution to energy dissipation ranked by a descending order of ceresine wax, flexible polymer-modified cement and polyurethane foam.